Antimony resistance and gene expression in Leishmania: spotlight on molecular and proteomic aspects - Rajamanthrilage Kasun Madusanka; Nadira D. Karunaweera; Hermali Silva; Angamuthu Selvapandiyan (Parasitology, 2024)
Leishmaniasis is a vector-borne parasitic disease caused by Leishmania parasites with a spectrum of clinical manifestations, ranging from skin lesions to severe visceral complications. Treatment of this infection has been extremely challenging with the concurrent emergence of drug resistance. The differential gene expression and the discrepancies in protein functions contribute to the appearance of 2 distinct phenotypes: resistant and sensitive, but the current diagnostic tools fail to differentiate between them. The identification of gene expression patterns and molecular mechanisms coupled with antimony (Sb) resistance can be leveraged to prompt diagnosis and select the most effective treatment methods. The present study attempts to use comparative expression of Sb resistance-associated genes in resistant and sensitive Leishmania, to disclose their relative abundance in clinical or in vitro selected isolates to gain an understanding of the molecular mechanisms of Sb response/resistance. Data suggest that the analysis of resistance gene expression would verify the Sb resistance or susceptibility only to a certain extent; however, none of the individual expression patterns of the studied genes was diagnostic as a biomarker of Sb response of Leishmania. The findings highlighted will be useful in bridging the knowledge gap and discovering innovative diagnostic tools and novel therapeutic targets.